Inhibition of Ubiquitin-specific Peptidase 8 Suppresses Adrenocorticotropic Hormone Production and Tumorous Corticotroph Cell Growth in AtT20 Cells - Jian, Fang-Fang (Chin Med J (Engl), 2016)
BACKGROUND: Two recent whole-exome sequencing researches identifying somatic mutations in the ubiquitin-specific protease 8 (USP8) gene in pituitary corticotroph adenomas provide exciting advances in this field. These mutations drive increased epidermal growth factor receptor (EGFR) signaling and promote adrenocorticotropic hormone (ACTH) production. This study was to investigate whether the inhibition of USP8 activity could be a strategy for the treatment of Cushing's disease (CD). METHODS: The anticancer effect of USP8 inhibitor was determined by testing cell viability, colony formation, apoptosis, and ACTH secretion. The immunoblotting and quantitative reverse transcription polymerase chain reaction were conducted to explore the signaling pathway by USP8 inhibition. RESULTS: Inhibition of USP8-induced degradation of receptor tyrosine kinases including EGFR, EGFR-2 (ERBB2), and Met leading to a suppression of AtT20 cell growth and ACTH secretion. Moreover, treatment with USP8 inhibitor markedly induced AtT20 cells apoptosis. CONCLUSIONS: Inhibition of USP8 activity could be an effective strategy for CD. It might provide a novel pharmacological approach for the treatment of CD.